Spouses' dependence across generations and pricing impact on reversionary annuities - Elisa Luciano; Jaap Spreeuw; Elena Vigna (Risks, 2016)
This paper studies the dependence between coupled lives, i.e., the spouses' dependence, across different generations, and its effects on prices of reversionary annuities in the presence of longevity risk. Longevity risk is represented via a stochastic mortality intensity. We find that a generation-based model is important, since spouses' dependence decreases when passing from older generations to younger generations. The independence assumption produces quantifiable mispricing of reversionary annuities, with different effects on different generations. The research is conducted using a well-known dataset of double life contracts.
Keywords: C12; C18; G22; J12; 330; stochastic mortality; generation effect; reversionary annuity; copula; goodness-of-fit